Konsep Kekekalan Akhirat: Komparasi Eskatologi Islam dan Kristen - Hebi Habibie (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Agus Mushtofa's concept of eternity in a more rational sense. The attributes of Allah that are used as an argument that the Hereafter is not eternal do not mean rejecting the understanding of the eternity of the Hereafter. However, the attributes of Allah do not want to limit the absolute ability of Allah. Attributes such as Wujud, Qidam, Baqa, Mukhalafatu lil Hawadisti, Qudrah and Iradah are qualities that make the eternal nature of the hereafter a different matter. This is different from the understanding of scholars in general who argue that the eternity of the hereafter is inviolable, while Agus Musthofa provides another understanding that the eternity of the hereafter depends on Allah. If Allah wants the hereafter to be eternal, then the hereafter will be eternal and if Allah removes the eternity of the hereafter, then the hereafter will be destroyed, both heaven and hell. Thoughts about the afterlife or the last day also exist in Christianity is not much different. If Muslims have a concept of life in the grave, so does the doctrine in Christianity. In the concept of Islam, humans who have died will enter the grave, in Christianity, if they die then when they enter the grave everything will be burned or purified with purgatory until the time of judgment arrives. Likewise heaven and hell in Islam and Christianity. If in Islam there are levels in heaven and hell according to their deeds. Christianity does not mention any levels of heaven and hell. In general, religious leaders in Islam and Christianity close the door on discussions about the eternal concepts of heaven and hell. Abstrak Konsep Agus Mushtofa tentang kekekalan dalam arti yang lebih rasional. Sifat-sifat Allah yang dijadikan sebagai argumentasi bahwasanya Akhirat tidak kekal bukan berarti menolak pemahaman tentang kekekalan akhirat. Akan tetapi dengan sifat-sifat Allah itu tidak ingin membatasi kemampuan mutlaq dari Allah. Sifat seperti Wujud, Qidam, Baqa, Mukhalafatu lil Hawadisti, Qudrah dan Iradah adalah sifat-sifat yang menjadikan sifat kekal akhirat menjadi hal yang berbeda. Hal inilah yang berbeda dengan pemahaman ulama pada umumnya yang berpendapat bahwasanya kekekalan akhirat tidak dapat diganggu gugat sedangkan Agus Musthofa memberikan pemahaman lain bahwasanya kekekalan akhirat tergantung pada Allah. Jika Allah berkehendak akhirat kekal, maka kekallah akhirat dan jika Allah mencabut kekekalan akhirat, maka musnahlah alam akhirat baik itu surga maupun neraka. Pemikiran tentang akhirat atau hari akhir juga ada dalam agama Kristen tidaklah jauh berbeda. Jika umat Islam ada konsep kehidupan dalam kubur, begitu juga doktrin dalam agama Kristen. Dalam konsep agama Islam, manusia yang telah meninggal akan memasuki alam kubur, dalam agama Kristen, jika meninggal maka tatkala memasuki alam kubur semuanya akan dibakar atau dimurnikan dengan api penyucian hingga tiba saat penghakiman. Begitu juga surga dan neraka dalam Islam dan Kristen. Jika dalam Islam ada tingkatan dalam surga dan neraka sesuai dengan amalannya. Agama Kristen tidak menyebutkan adanya tingkatan dalam surga dan neraka. Pada umumnya para pemuka agama dalam agama Islam dan Kristen menutup pintu diskusi tentang konsep kekekalan surga dan neraka.